Preliminary in vitro and ex vivo evaluation of afzelin, kaempferitrin and pterogynoside action over free radicals and reactive oxygen species - Vellosa, José Carlos Rebuglio; Regasini, Luis Octavio [UNESP]; Belló, Caroline; Schemberger, Josiane Aparecida; Khalil, Najeh Maissar; Morandim-Giannetti, Andreia De Araújo; Bolzani, Vanderlan da Silva [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Oliveira, Olga Maria Mascarenhas de Faria [UNESP] (Springer Nature, 2014)
Biological activities of flavonoids have been extensively reviewed in literature. The biochemical profile of afzelin, kaempferitrin, and pterogynoside acting on reactive oxygen species was investigated in this paper. The flavonoids were able to act as scavengers of the superoxide anion, hypochlorous acid and taurine chloramine. Although flavonoids are naturally occurring substances in plants which antioxidant activities have been widely advertised as beneficial, afzelin, kaempferitrin, and pterogynoside were able to promote cytotoxic effect. In red blood cells this toxicity was enhanced, depending on flavonoids concentration, in the presence of hypochlorous acid, but reduced in the presence of 2,20 -azo-bis(2-amidinopropane) free radical. These flavonoids had also promoted the death of neutrophils, which was exacerbated when the oxidative burst was initiated by phorbol miristate acetate. Therefore, despite their well-known scavenging action toward free radicals and oxidants, these compounds could be very harmful to living organisms through their action over erythrocytes and neutrophils.
Keywords: Flavonoids; Red blood cells lysis; Oxidative burst; Antioxidants; Pterogyne nitens; Free radicals; Int